Effect of Surfactant Polyvinyl Pyrrolidone on the Properties of Microporous Carbon Nanospheres Reinforced Magnesium Matrix Composites - Jin, Lin (Nanomaterials (Basel), 2020)
Microporous carbon nanospheres (PCNS)-reinforced magnesium (Mg) composites were prepared using polyvinyl pyrrolidone (PVP) as surfactant and PCNS as reinforcement. The influence of PVP treatment and the effectiveness of PCNS on the mechanical properties of Mg-based composites were investigated. The results show that the PCNS can enhance the properties of the Mg matrix. Moreover, the PVP can effectively improve the dispersion of PCNS in the Mg matrix but had a negative influence on the tensile properties of composites. The MgO films with high tensile strength were produced between matrix and reinforcement after removing PVP, which effectively promotes the interface compatibility and improves the properties of the composite. The tensile yield strength and specific strength of PCNS-reinforced Mg matrix composite exhibited 177 MPa and 102.4 × 103 N∙m/kg, respectively, which were 77% and 78% higher than those of the Mg matrix.